HUBUNGAN PEMBERIAN ASI EKSKLUSIF DENGAN KEJADIAN DIARE PADA ANAK DI RS MYRIA - Rini, Maria Tarisia (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2018)
The highest diarrhea child mortality rate occurred at 6-11 months. Diarrhea can be prevented by exclusive breastfeeding. Breastfeeding is the best food for babies because it contains nutrients needed for growth and development. Colostrum in breast milk contains 10-17 times more immune than mature milk. The coverage of exclusive breastfeeding in the world is still low at 38%. The achievement of exclusive breastfeeding in Indonesia in 2017 was 35.73%, still far from the target of 80%. The research design used is an analytical survey with a retrospective approach. The number of samples in the study were 32 respondents with purposive sampling technique. Statistical analysis using chi square with significance level α (0.05). The results showed that there was a relationship between exclusive breastfeeding and the incidence of diarrhea in children (p value 0.030 <0.05). The conclusion of this study is that exclusive breastfeeding can provide immunity to children to prevent diarrhea. The recomended that can be given is that nurses begin to promote exclusive breastfeeding. Keyword: Exclusive breastfeeding, diarrhea